Environmental influences on the successful regeneration of pine-oak mixed forests in the Qinling Mountains, China. Issue 4 (18th May 2016) - Chai, Zongzheng; Wang, Dexiang
ABSTRACT: Understanding the factors that allow the successful regeneration of species is a key step toward the conservation and management of forests. In this study, canonical correspondence analysis was used to examine the relationships between the distribution of the regenerating species in pine-oak mixed forests and 18 environmental factors of topography, soil properties, and forest characteristics in seedlings and saplings in the Qinling Mountains in China. A generalized additive model was used to fit the response of the density of the regenerating species to the various environmental factors. Variation partitioning in both seedling and sapling stories indicated that the order of importance was soil properties > forest characteristics > topography. The distribution of seedlings and saplings was mainly influenced by slope gradient, shrub cover, and available phosphorus. Herb cover and total nitrogen level were major environmental factors affecting the density of the regenerating seedlings, but total potassium level and elevation were significant variables for saplings. Not all seedlings were able to establish successfully, perhaps due to stress from the external environment and the heterogeneity of the light availability in the understory as the forest developed. Appropriate thinning of stands with higher densities and closed canopies is expected to produce gaps and promote the natural regeneration of pine-oak mixed forests in the Qinling Mountains.